Employer's prerogative in the context of outsourcing - Ten Berge, Susanne Francijna Maria (University of the Western Cape, 2013)
Magister Legum - LLM === This research paper investigated whether there are any limitations or restraints in the Labour Relations Act 66 of 1995, which possible keeps an employer from outsourcing functions or parts of a business to a third party. === South Africa